The effect of benzodiazepine and nonbenzodiazepine prescriptions for diabetes mellitus type 2 in elderly Taiwanese with depressive symptoms. Issue 2 (27th April 2015) - Tsai, Min‐Ling; Huang, Chien‐Ning; Lai, Yung‐Rung; Chang, Horng‐Rong; Chiou, Jeng‐Yuan
Abstract: Background: This study examined the relationship between depression, benzodiazepine (BZD)/nonbenzodiazepine hypnotics (non‐BZD), and other risk factors in a national sample of Taiwan's elderly diabetic patients. Methods: Data were drawn from the 2005 Taiwan National Health Interview Survey and adults aged 65 years and older. A total of 1331 subjects were included in this study. The Chinese version of Center for Epidemiologic Studies Depression Scale was used to evaluate patients' depression symptoms. Results: The rates of depression in the diabetes mellitus (DM) and non‐DM groups were 13.5% (39/288) and 9.8% (102/1043) and the average ages were 73.7 and 73.4 years, respectively. In multivariate regression, the odds ratio of depression was 1.66‐fold higher among BZD/non‐BZD users (95% confidence interval: 1.10–2.51, model 2) than among those without BZD/non‐BZD use. In addition, hyperlipidaemia, poor physical function, and antidepressant use were associated with a higher risk of depressive symptoms. Meanwhile, a monthly household income of NT30 000–NT49 999, exercise, and betel chewing were associated with a lower risk of depression. We performed an additional logistic analysis for which the odds ratio of depression significantly increased to 1.52 in non‐DM elderly patients (95% confidence interval: 1.06–2.19) who were prescribed BZD/non‐BZD. In contrast, there was no significant difference in the odds ratio of depression in the DM elderly regardless of BZD/non‐BZD use, although there was a slight tendency for depression among those who used BZD/non‐BZD. Conclusion: Depression in non‐DM Taiwanese elderly patients was found to be associated with BZD/non‐BZD use, whereas depression in DM Taiwanese elderly patients was not found to be associated with BZD/non‐BZD use.